2021
DOI: 10.20882/adicciones.1559
|View full text |Cite
|
Sign up to set email alerts
|

Guía de práctica clínica para el tratamiento farmacológico y psicológico de los pacientes adultos con depresión y un diagnóstico comórbido de trastorno por uso de sustancias

Abstract: Guía de práctica clínica para el tratamiento farmacológico y psicológico de los pacientes adultos con depresión y un diagnóstico comórbido de trastorno por uso de sustancias Clinical practice guideline on pharmacological and psychological management of adult patients with depression and a comorbid substance use disorder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Our ndings are consistent with several other randomized clinical trials for PTSD pharmacotherapy which include: sertraline 98 , paroxetine 99 , uoxetine 100 and venlafaxine 100 . However, a recent clinical practice guideline study suggested that patients with depression and cannabis use, should not be treated with venlafaxine 101 . But the need for more de nitive larger, multisite, randomized clinical trials is essential.…”
Section: Montelukastmentioning
confidence: 99%
“…Our ndings are consistent with several other randomized clinical trials for PTSD pharmacotherapy which include: sertraline 98 , paroxetine 99 , uoxetine 100 and venlafaxine 100 . However, a recent clinical practice guideline study suggested that patients with depression and cannabis use, should not be treated with venlafaxine 101 . But the need for more de nitive larger, multisite, randomized clinical trials is essential.…”
Section: Montelukastmentioning
confidence: 99%